REFLECTION OF LANGUAGE AND CULTURE IN THE LINGUISTIC LANDSCAPE OF THE WORLD (Academicia Globe: Inderscience Research, 2023)
Summarizing the views on the concept and its definitions in linguistics allows us to come to the following conclusion: the concept is a unit of collective knowledge with a linguistic expression and a defined ethno-cultural identity. The concepts that have come to the attention of researchers are constantly expanding. Today, there are many ways and methods by which you can explore this or that concept. In addition to certain types of material concepts, it allows to distinguish new types.